Level of Stress among Medical Students of Selected Non Government Medical College (Journal of Brahmanbaria Medical College, 2026)
Background: Stress among doctors is a major concern that can direct to physical and mental illness and can harm the quality of patient care. This stress starts from their student life. This study assessed stress and its associated factors among Medical students from first year to fifth year. Materials and methods: This was a cross sectional study based on level of stress among Medical students. Respondents were selected on purposive sampling technique according to the availability and consent. Face-toface interviews were conducted using interviewer administered semi-structured pretested questionnaire which was developed using Medical Students Stressor Questionnaire and The Perceived Stress Scale (PSS). Results: This study was conducted among194 Medical Students, among them 44 students from 1st year, 54 students from 2nd year, 46 students from 3rd year, 35 students from 4th year, 15 students from 5th year. Among them 75.3% were from nuclear family. Among 194 respondents 80.4% had experience mild to moderate stressors as perceived by the respondent, 4.6% respondent experience severe stressor and others (14.9%) had no experience of stressor. More than 94.8% respondents were Very High Severe health concerns according to PSS scale. Most students (184 out of 194) scored more than 20 on the PSS, indicating higher perceived stress. The majority of those students (147) had stress questionnaire scores between 55 and 81. The p-value (0.676) for the Pearson Chi-Square test is greater than 0.05, indicating no significant association between the Student Stress Questionnaire categories and PSS scores. Noted that 2 cells (33.3%) have expected counts less than 5, which slightly violates Chi-square test assumptions. Conclusion: Though it is not significant but its confirm that maximum respondant experience severe stressor and they were Very High Severe health concerns according to PSS scale.JBRMC, Volume 08 Issue 01 January 2026 ; 32-36